A Contrastive Analysis Between English and Indonesian Syllable Structure - Habib Syukri Nst (Departement of Mathematics Education, 2022)
Words can be cut up into units called syllables. Humans seem to need syllables as a way of segmenting the stream of speech and giving it a rhythm of strong and weak beats, as we hear in music. Syllable structure donot serve any meaning-signalling function in linguistic, they exist only to make speech easier for the brain to process. A word contains at least one syllable. In most theories of phonology, the general structure of a syllable (σ) consists of three segments: Onset (ω) consonant, obligatory in some languages, optional or even restricted in others. Nucleus (ν) sonorant, obligatory in most languages. Coda (κ)consonant, optional in some languages, highly restricted or prohibited in others. The similarities between English and Indonesian syllable structure, that is the components of English and Indonesian syllable structure consist of an onset, a nucleus, and a coda. The disisimilarities between English and Indonesian syllable structure, that is there are two combinations of stop consonant in taking the Indonesian onset cluster which cannot be found in English syllable structure. The combinations are stop /p// with stop /t/ and stop /p/ with fricative /s/